Association of Clinical Parameters with Dengue Fever and Co-infection in a Tertiary Care Hospital (Eastern Medical College Journal, 2025)
Background: Dengue is becoming a more serious public health issue in Bangladesh. It consistently has a particularly harmful effect on this country almost every year. Patients with classic dengue typically exhibit fever, myalgia, arthralgia, retro-orbital discomfort and rash in the body. Additionally, hemorrhagic manifestations, with or without shock, can be seen in dengue infections. The aim of the study is to investigate the relationship of clinical parameters and laboratory findings with dengue and co-infected patients.Materials and Methods: The prospective observational study was conducted from July to December 2023 at the department of Paediatrics, Eastern Medical College and Hospital, Cumilla. The study comprised 197 patients aged 2 to 18 years admitted in this hospital with a fever lasting 84 hours or more and whose blood samples were positive for NS1 or IgM against dengue and screened for other co-infections. The study excluded patients with hemoglobinopathies, those who had received several transfusions, those suffering from chronic conditions and those who refused to participate.Results: Among 197 patients NS1 was positive in 175 (89%) samples and Dengue IgM was positive in 22 (11%) samples. Besides, among 197 cases 160 (81%) were diagnosed with dengue and 37 (19%) were diagnosed with co-infection. By gender, 68.75% were males and 31.25% were females in dengue cases. Vomiting, nausea and cough were significant features in dengue and co-infection. Urinary pus cell >10/HPF and Widal test titer ≥1:320 were statistically significant in the co-infection group.Conclusion: Dengue fever can affect children irrespective of their age or nutritional status. Dengue with co-infection was 19% in this study. This study re-emphasizes the fact that clinicians should be aware that co-infection with dengue and initiate appropriate therapy to decrease morbidity and mortality.Eastern Med Coll J. July 2025; 10 (1): 29-32